Upscaling methane hydrate dissociation kinetic model during depressurisation - Yang, J; Xu, Q; Liu, Z; Shi, L; Lei, T; Luo, KH (Elsevier BV, 2023)
In the present work, a pore-scale numerical simulation of methane hydrate dissociation by depressurisation is conducted to analyze the effect of heat and mass transfer on the dissociation rate for scaling up the kinetic model at the representative element volume (REV) scale. The mass transport limitation shows that the hydrate dissociation preferred to occur near the gas phase. The effective reaction surface area is introduced to measure the exposed hydrate surface to the gas phase during gas and water migration and is modelled as a function of local hydrate and water saturation and hydrate pore habits. Heat transport limitation is computed with the one-temperature model due to the local thermal equilibrium. Compared to the pore-scale simulation, the proposed REV-scale kinetic model predicts dissociation rates with a relative error of less than 10%, which is expected to increase the precision of the hydrate recovery forecast.